Optimizing the Goods Distribution Process with a Lean Distribution Approach CV Anugerah Hasil Abadi - Achmad Gufron; Dwi Sukma Donoriyanto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
In the distribution industry, operational efficiency is essential to improve competitiveness and customer satisfaction. This study aims to optimize the distribution process of goods at CV Anugerah Hasil Abadi by implementing the Lean Distribution approach. The Value Stream Mapping (VSM) method is used to identify major waste in the distribution process, while the 5 Whys method is used to find the causes. The results of the study showed five activities with the highest time waste, namely storing goods in the warehouse (1440 minutes), loading goods into trucks (180 minutes), the process of unloading goods from trucks (180 minutes), checking goods according to sales orders (34 minutes), and the manager's signature process (30 minutes). The implementation of improvement solutions, such as the use of a warehouse management system (WMS), investment in loading and unloading equipment, and process digitalization, succeeded in reducing distribution time by 720 minutes, from 4260 minutes to 3540 minutes. In addition, the Process Cycle Efficiency (PCE) increased from 49.91% to 60.06%. These results prove that the implementation of Lean Distribution can improve operational efficiency and reduce waste in the distribution process.